EXPLORING THE EXPERIENCES OF TEACHERS AND MI STUDENTS IN USING AI-BASED TECHNOLOGY TO IMPROVE DIGITAL LITERACY AND PEDAGOGICAL COMPETENCE - Mustofa, Arif; Fajrin, Ajeng Lilananda (Sekolah Tinggi Agama Islam Al Hidayah, 2025)
Background: The digital era, technology, especially artificial intelligence (AI), plays a crucial role in education, including at the elementary and secondary levels. Applications such as ChatGPT are considered capable of improving the quality of learning through interactive features tailored to student needs. Purpose: However, the application of AI in Islamic elementary schools (MI) remains limited, particularly in its impact on teachers' pedagogical competence and students' digital literacy. Method: This study employed a qualitative approach to explore and understand the experiences and perceptions of teachers and students at Islamic elementary schools (Madrasah Ibtidaiyah) regarding the use of artificial intelligence (AI)-based technology, specifically ChatGPT, in learning to improve students' digital literacy and teachers' pedagogical competence. Result: The results of this study, including the implementation of an AI technology workshop at MI Bina Umat, demonstrated an increase in teachers' competence in planning and implementing adaptive learning. Conclusion: The use of Canva and ChatGPT proved effective in developing interactive media and preparing learning evaluations. Furthermore, students' digital literacy also improved, as evidenced by their ability to independently use digital information and utilize AI to support the learning process. Implication: The integration of AI in elementary schools is an innovative solution to address the challenges of modern education.